Implementasi Kurikulum Merdeka dalam Meningkatkan Prestasi Belajar Siswa di MTsS Darussalam Sengon Jombang - Sa'adah, Dewi Mambaus; Sirojudin, Didin (YASIN, 2025)
This study examines the implementation of the Merdeka Curriculum at MTSs Darussalam Sengon Jombang and its impact on student achievement. The method used in this study is a qualitative descriptive method. The Merdeka Curriculum prioritizes freedom of thought and creativity, aiming to develop lifelong learners who embody the Pancasila student profile. Key factors supporting this implementation include strong leadership from the principal, teacher training workshops, and curriculum flexibility, which allows educators to adjust learning to meet student needs. However, this study also identified significant challenges, such as teachers' limited understanding of the curriculum and students' difficulties in adapting to the new independent learning method. The study concluded that while the Merdeka Curriculum has the potential to improve student performance, significant obstacles must be overcome to fully realize its benefits. The implementation process is structured into three interconnected stages: planning, implementation, and evaluation, with an emphasis on formative assessment during the learning process and summative assessment after completion of the material. Despite these efforts, this study shows that there has been no significant improvement in student academic performance, highlighting the need for further investigation into the challenges of implementing this curriculum.